THE RISE OF NATIONAL PLUS SCHOOL IN INDONESIA â€“ EDUCATION FOR PARENTS AND GOVERNMENT - Rinaldi, Indra; Saroh, Yam (English Department FBS UNP, 2016)
PENINGKATAN SEKOLAH NASIONAL PLUS DI INDONESIA â€“ PENDIDIKAN UNTUK ORANG TUA DAN PEMERINTAHÂ AbstractThis paper explores a social movement that has happened in Indonesia in the field of education. It also explores its effect to â€˜educateâ€™ the government as well as most parents in the country about the education quality in Indonesia. The exploration focuses on how this new concept of education which is referred as National Plus school was introduced to society that has encouraged many people to develop the schools with the same (national plus) concept. It also focuses on the parents who have learnt more about the new education system then participate in it by sending their children to such the schools. Not only in the grass root level, has it also focused onthe factors of the government who was indirectly forced to respond this phenomenon by developing international-leveled school. This movement has happened nationally within the last 10 years and has changed the national curriculum as well as educational system, including the recognition of special needs students among the government schools. This movement has changed the old conventional style of education that was commonly found in Indonesian national schools.Keywords: adult learning, National Plus, national education, movementAbstrakArtikel ini membahas tentang sebuah gerakan sosial yang terjadi di Indonesia di bidang pendidikan. Artikel ini juga menggali pengaruh gerakan social terhadap 'mendidik' pemerintah serta orang tua di negeri ini tentang kualitas pendidikan di Indonesia. Eksplorasi berfokus pada konsep pendidikan baru yang disebut dengan istilah â€œSekolah Nasional Plusâ€ yang diperkenalkan kepada masyarakat yang telah mendorong banyak orang untuk mengembangkan sekolah dengan konsep yang sama (nasional plus). Artikel ini juga berfokus pada orang tua yang telah belajar lebih banyak tentang sistem pendidikan baru yang kemudian melibatkan mereka berpartisipasi di dalamnya dengan mengirimkan anak-anak mereka kesekolah-sekolah tersebut. Tidak hanya di tingkat dasar, tetapi juga difokuskan pada faktor-faktor pemerintah yang secara tidak langsung dipaksa untuk menanggapi fenomena ini dengan mengembangkan sekolah berstandar internasional. Gerakan ini terjadi secara nasional dalam jangka waktu 10 tahun dan telah mengubah kurikulum nasional serta sistem pendidikan nasional, termasuk pengakuan dari siswa berkebutuhan khusus di antara sekolah-sekolah pemerintah. Gerakan ini telah mengubah gaya konvensional pendidikan yang umum ditemukan di sekolah-sekolah nasional di Indonesia.Kata kunci: pembelajaran orang dewasa, National Plus, pendidikan nasional, gerakan